Legal Protection of Patient Rights in Indonesia - Istiana Heriani; Gunarto Gunarto; Anis Masdhurohatun (Sriwijaya Law Review, 2019)
This study examines the legal protection of patient rights in health services in Indonesia. The aims of the study are to find out how the legal protection of patients as consumers in receiving health services and what factors affecting the legal protection of patients’ rights in receiving health services. The method employed in this study is a normative study by analysing data obtained from library. The data gathered are in form of secondary data. All the data collected are analysed descriptive qualitative. The problem raised herein is Law Number 44/2009 Concerning the Hospital is not fully well implemented. The results showed that there were many factors influent the effectiveness of Law Number 44/2009 above. The conclusion drawn up that the malpractice in terms of providing medical care may cause disharmony between physicians and patients; the facilities and infrastructures in the health care provided for in the hospital do not support the patients’ rights to obtain health care. Any responsibility borne to the hospital may only in the case of the patients suffered from the malpractice. Should this happen the patients can submit any formal complain to the Court